2008
DOI: 10.1111/j.1365-3032.2008.00617.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bacteria on nutritional status and reproductive success of the Mediterranean fruit fly Ceratitis capitata

Abstract: Mediterranean fruit flies ( Ceratitis capitata Wiedemann, Diptera: Tephritidae) harbor a community of diazotrophic bacteria in their digestive system. The present study aims to test the hypothesis that bacteria contribute to fly fitness by enhancing copulatory success and egg production in males and females, respectively. After eclosion, flies were fed a full diet containing peptides, sugar and minerals, or a sugar diet, lacking peptides. Subgroups from each diet were fed a mixture of the antibiotics ciproflox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
131
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 124 publications
(136 citation statements)
references
References 44 publications
5
131
0
Order By: Relevance
“…A previous study has shown that Enterobacteriaceae were dominant intestinal commensal bacteria in the gut of B. dorsalis , as well as in several other tephritids, such as Dacus (Drew and Lloyd, 1991), Anastrepha (Kuzina et al, 2001) and Ceratitis (Behar et al, 2008). These bacteria may contribute to nitrogen fixation (Behar et al, 2005), pectinolysis (Behar et al, 2008), male copulatory success (Ben-Yosef et al, 2008) and may also have an indirect contribution to host fitness by preventing the establishment or proliferation of pathogenic bacteria (Behar et al, 2008). Members of the Leuconostoc genus ferment fructose (Ljungdahl, 1962), suggesting that these microbes may play a symbiotic role in promoting insect digestion of fruits or other plant materials (Corby-Harris et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study has shown that Enterobacteriaceae were dominant intestinal commensal bacteria in the gut of B. dorsalis , as well as in several other tephritids, such as Dacus (Drew and Lloyd, 1991), Anastrepha (Kuzina et al, 2001) and Ceratitis (Behar et al, 2008). These bacteria may contribute to nitrogen fixation (Behar et al, 2005), pectinolysis (Behar et al, 2008), male copulatory success (Ben-Yosef et al, 2008) and may also have an indirect contribution to host fitness by preventing the establishment or proliferation of pathogenic bacteria (Behar et al, 2008). Members of the Leuconostoc genus ferment fructose (Ljungdahl, 1962), suggesting that these microbes may play a symbiotic role in promoting insect digestion of fruits or other plant materials (Corby-Harris et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…A third diet contained sugar, minerals and NE amino acids as the sole source of amino nitrogen. Antibiotics (piperacillin, Fluka), which had previously been used effectively to suppress the gut bacterial population in the Mediterranean fruit fly (Ben-Yosef et al 2008a), were added to the diet of half of the females in each of the three groups in order to eliminate the bacterial component of the gut microbiota.…”
Section: Methodsmentioning
confidence: 99%
“…A similar study examining the fruit fl y C. capitata showed that removing the commensal gut bacteria results in no difference of fecundity but an increase in oviposition rate (Ben-Yosef et al, 2008). Although this effect is slightly different to the one we have shown in D. subobscura as overall fecundity is not shown to be different, it reaffi rms that bacteria must play an important part in post-mating female reproductive physiology and behaviour.…”
Section: Discussionmentioning
confidence: 39%
“…Individuals were either fed normally, and therefore had a "typical" gut bacterial content, or they were fed with antibiotic-supplemented food. Adding antibiotics to the rearing medium is a standard method of suppressing gut bacteria (Koukou et al, 2006;Ben-Yosef et al, 2008;Sharon et al, 2010;Lizé et al, 2014). However, in order to confi rm that our technique resulted in suppression of the gut microbiota, we analysed the bacterial content of the D. subobscura gut from both the normal and the streptomycin reared diets.…”
Section: Confi Rmation Of Suppressed Gut Microbiotamentioning
confidence: 99%